GAYA BAHASA HIPERBOLA DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI (KAJIAN ANALISIS ISI) - Poppy Irda Arianto; Sainil Amral; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze the function of hyperbolic language style in the novel Negeri 5 Menara by Ahmad Fuadi. The analysis of this research will answer the research questions and research objectives, namely, to describe the function of hyperbole, which includes the function of giving a dramatic impression, composing sentences beautifully, and emphasizing emotions. This research will illustrate how the function of hyperbolic language style functions as a strength in literary works, especially in novels. The research method used to collect and analyze research data, researchers used qualitative descriptive methods. With this research method, researchers can describe the function of hyperbole language style from the three functions studied. With this research method, researchers can describe the results of research on how the function of hyperbolic language style is to give a dramatic impression, compose sentences beautifully, and emphasize emotions in the novel. The results of the research can be explained that the function of hyperbolic language style in the novel Negeri 5 Menara by Ahmad Fuadi tends to be the function of hyperbolic language style in giving a dramatic impression to the novel. This can be seen in the quotes found in the function of providing a dramatic impression of 50 quotes. Apart from that, there are 28 quotes to compose sentences beautifully. And the function provides emotional emphasis for 22 quotes. In other words, the total number of hyperbolic stylistic functions found in this novel is 100 quotations.